Transfected rat high-molecular-weight neurofilament (NF-H) coassembles with vimentin in a predominantly nonphosphorylated form - Chin, SS (J Neurosci, 1990)
A fully encoding cDNA for the high-molecular-weight rat neurofilament protein (NF-H) has been isolated from a lambda gt11 library, sequenced and subcloned into eukaryotic expression vectors. Sequence analysis shows that rat NF-H has an overall homology of 72 and 88% with human and mouse NF-H, respectively. The head and rod domains are almost entirely identical, and the divergences are due to differences in the long C-terminal extensions of the molecule. The consensus phosphorylation sequence for neurofilaments Lys-Ser-Pro (KSP) is present 52 times. The predicted molecular mass of the protein is 115 kDa, 42% lower than that observed by SDS-PAGE. Upon transfection into vimentin-containing fibroblasts, such as L tk-, L929, and 3T6 cells, NF- H is seen distributed with vimentin by light and electron microscopic examinations indicating that copolymers of NF-H and vimentin are formed in these cells. Only a negligible proportion of the cells is positive when stained with a number of antibodies directed against phosphorylated NF-H epitopes. This is in contrast with the middle molecular weight NF protein (NF-M) transfected into L tk- and L929 cells, which can readily be detected by antibodies against phosphorylated neurofilament epitopes. The mobilities of the transfected protein on 1- and 2-dimensional gels confirm that NF-H is predominantly in a nonphosphorylated form. These results indicate that phosphorylation of NF-H, but not NF-M, on the KSP sequence is due to protein kinases, which are not present in fibroblasts and are presumably NF-H specific. The stable NF-H-expressing cell lines can therefore be used to study these putative neurofilament kinases in vitro and in vivo.